Studying the effect of some factors on the high incidence of uterine fibroid in Libyan women - Ashour, Fathia M. Ben; Eljadi, Abdulmonem M.; Gregni, Nadia B.; Alkali, Afaf A.; Husien, Walid M. Ramadan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine fibroids (UF), they are also called uterine leiomyoma’s or myomas, are benign growth of smooth muscle of the uterus or womb .The body of uterus consists of 3 layers ;serosa, myometrium and endometrium. The myometrium is composed of bundles of smooth muscle and connective tissue. This study performed to investigate the reasons of high incidence of UF among Libyan women. Methods: The Factors implicated in this case are analyzed using questionnaire on a random patient sample (152 cases) within (2010-2014) from the archive of Aljalaa hospital. Results: Results show that, UF could affect women in young ages and above 40 years as well (P = 0.14). Marital status and the race of the patients significantly affect the rate of UF. The number of UF increased among married and white women comparing with single one and black one (P = 0.00) respectively. UF cases in the women holding O+ blood group were significantly higher than other groups (P=0.00). The educated women exhibit significant decrease in the UF incidence compared with less education status (P=0.00). Both normal delivered mode women and those received contraception pills showed a significant high rate of UF comparing with caesarian cut and with non-treated group (P=0.00), respectively. Menorrhagia was significantly higher than abdominal pain and infertility. Recurrent and family history was invaluable in UF incidence. Its ratio was significantly higher among women with no previous history and who have no family history (P=0.00). Myomectomy was significantly different from other choices; trans-abdominal hysterectomy and others (P=0.00). Conclusions: According to our results, marital status, hormones disturbances, life style including stress factors, race and knowledge about the case are the most implicated causes in the incidence of the case. Further studies on the ultra-structural level (Model) are needed to verify the possible role/s for genes.